CHONDROECTODERMAL SYNDROME - Jan, Asad Ullah; Ahmad, Sajjad; Cheema, Tehseen Ahmad; Ullah, Farman; Waqar, Muhammad; Hussain, Baqir (Journal of Ayub Medical College Abbottabad, 2018)
Chondroectodermal syndrome or Ellis Van Creveld (EVC) is a rare autosomal recessive congenital disorder. It was first described by Richard W.B.Ellis and Simon Van Creveld in 1940. Parental consanguinity is present in about 30% of the cases. A large number of cases were reported in Amish population of Lancaster County, Pennsylvania USA and also in Aboriginal community of Australia in 1964. The incidence in Amish population is 1/5000 live births and in general population 7/1,000,000. There are only 150 cases reported worldwide. The principal feature of this syndrome is a tetrad of disproportionate dwarfism, ectodermal dysplasia, bilateral postaxial polydactyly and congenital heart defects. Keywords: Chondroectodermal dysplasia; Ellis Van Creveld syndrome; Postaxial Polydactyly